GURU KREATIF, SEKOLAH PRODUKTIF : PROGRAM PENGEMBANGAN TEACHERPRENEUR SEBAGAI WIRAUSAHAWAN EDUKATIF DI ERA DIGITAL - Fariha azzahra; Dela Tri Mulyani (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background: The current digital era requires teachers to have broader skills, including entrepreneurship, so that students can understand the learning provided and create a pleasant classroom situation. Teachers actually have the opportunity to develop productive businesses that can support sources of income and support learning, but there are still many challenges faced by teachers such as limited time and workload, lack of knowledge and entrepreneurial skills. Objective: By providing teacherpreneur knowledge, teachers will have an entrepreneurial spirit that can improve the quality of education and empower the economic potential of teachers in a sustainable manner. Method: This community service is carried out by providing socialization and training to teachers at State Junior High School 3 Satu Atap Tawangharjo. Results: Community service through socialization and training is able to encourage teachers to not only become teachers, but also become social problem solvers in the school environment through a sustainable entrepreneurial approach. Conclusion: The concept of teacherpreneur is able to improve the welfare and strengthen the creativity of teacher competence in technology.